Georgia Seventh and Eighth Reviews Under the Stand-By Arrangement, and Requests for Waivers of Nonobservance of Performance Criteria and Rephasing of Purchases-Staff Report; Staff Statement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Georgia (IMF Staff Country Reports, 2011)
Real GDP growth for 2010 has been revised upward to 6.3 percent, and annual CPI inflation has increased to about 10 percent. End-December performance criteria (PC) are expected to be met, with the exception of the fiscal deficit and general government expenditure targets owing to the late disbursement of budget grants and disbursements under a project loan on-lent by the government, which came in earlier than the authorities anticipated. Policies are on track and have broadly delivered on program objectives